Sorting through the motor performance abilities maze - Brooks, C. M. (New Studies in Athletics, 2013)
ABSTRACT A motor skill is learned while a motor ability is a genetic characteristic. An athlete's success depends on how well foundational motor performance abilities - endurance, strength, speed, coordination and flexibility - are applied to performing the movement units encompassed in the skill required for his/her event. For the purpose of training programme design it is important to understand how these foundational abilities and derived motor performance abilities, such as anaerobic endurance, muscular endurance, power, speed of response, and acceleration, fit together. However, discussions in this area often slip into a confusing jumble of terminology. In this paper, the author, an experienced coach educator, offers a general guide to this maze. The Bös motor performance abilities model is used to classify motor abilities as either energetically determined or information oriented. It is then shown how the foundational motor performance abilities contribute to the derived motor performance abilities. Finally, using hurdling as an example, the process of conducting a needs analysis of an event for its relevant motor performance proficiencies is illustrated.